PENGARUH INDEPENDENSI, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA AUDITOR YANG BEKERJA DI KANTOR INSPEKTORAT KABUPATEN PELALAWAN) - Sahrani S Almaida; Rasuli Rasuli; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aimed to examine the effect of independence, emotional intelligence, spiritual intelligence and organizational commitment to auditor performance. sample of this study is the auditors who working in the Inspectorate office Pelalawan district at 2020. The sampling method is used purposive sampling methode with total 39 respondents and the population 45 peoples who used in this study. The data source used in the study was the primary data. Analysis of data is carried out using multiple regression analysis with the program of SPSS version 23.0 windows. The result proved that: (1) independence had a effect on auditor performance. (2) emotional intelligence had a effect on auditor performance. (3) spiritual intelligence had not effect on auditor performance. (4) organizational commitment had a effect on auditor performance.Keywords : Independence, Emotional Intelligence, Spiritual Intelligence, Organizational Commitment, Auditor Performance